An Analysis of Mainstream Animation Education in Japan and the United States Using Computer 3D Technology. (July 2020) - Chen, Danping
Abstract: As an important part of culture and entertainment, animation is also a form of artistic expression with entertainment and educational functions. The application of computer 3D technology makes the animation more vivid and expressive. This paper USES computer 3D technology to analyze the entertainment and educational functions of American and Japanese animation, as well as the educational significance of American and Japanese animation. This paper points out that computer 3D technology not only creates new cultural connotation of American and Japanese animation content, but also is one of the important factors of its educational significance.